2020
DOI: 10.1177/0145561320950491
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Impact of Nasal Lavages During Viral Infections Such as SARS-CoV-2

Abstract: Much has been stated about the potential risks of nasal lavages (NL) during the coronavirus disease 2019 (COVID-19) pandemic for COVID-19 patients and surrounding people. Several otolaryngological societies recommended to limit NL, supposing it may be associated with viral spread to lower airway. 1 On the contrary, recent studies suggested that NL may be beneficial in upper viral respiratory infectious diseases. In order to take stock of this issue, we conducted a short literature review to address 4 main ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Multiple studies have demonstrated immediate viral load reductions in vitro and in vivo with direct oral or nasal application of antivirals, [8][9][10] or the theoretical benefit of lavaging and gargling. [36][37][38] One study of povidone-iodine gargles and sprays in 24 patients did not show a significant reduction in viral load, but the age difference of 23 years between control and intervention groups calls randomization into question . 39 An interim analysis of a twice daily nasal irrigation trial in 45 young adults showed initial clinical improvement, 17 but was ultimately underpowered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have demonstrated immediate viral load reductions in vitro and in vivo with direct oral or nasal application of antivirals, [8][9][10] or the theoretical benefit of lavaging and gargling. [36][37][38] One study of povidone-iodine gargles and sprays in 24 patients did not show a significant reduction in viral load, but the age difference of 23 years between control and intervention groups calls randomization into question . 39 An interim analysis of a twice daily nasal irrigation trial in 45 young adults showed initial clinical improvement, 17 but was ultimately underpowered.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have demonstrated immediate viral load reductions in vitro and in vivo with direct oral or nasal application of antivirals,(7-9) or the theoretical benefit of lavaging and gargling. (36)(37)(38) However, a small study of gargles and sprays of effective povidone-iodine did not show a significant reduction in viral load,(39) nor were clinical differences seen in a small randomized trial using twice daily nasal irrigation without an effective virucidal. (17) Multiple commentaries have supported the concept and safety(37) of debridement.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published review focused on the vulnerability of SARS-CoV-2 regarding NaCl and presented this in detail [ 8 ]. This type of antiviral activity, utilized against a wide range of viral infections, can be augmented by the availability of NaCl [ 9 , 10 ]. Virus particles are sensitive to dehydrating conditions (as exerted by salt) because they need structurally unmodified surface proteins and nucleic acids for the binding and infection of target cells.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis reveals that many of these drugs are linked to ongoing efforts against COVID-19: several top-ranked BSAs from our matrix decomposition model are part of ongoing clinical trials for COVID-19, or are even already approved for compassionate use in COVID-19 patients [56][57][58][59] ; several top-ranked drugs from our network medicine approach have also shown efficacy either as therapeutic alternatives or as instruments for reducing risk of infection and transmission. [60][61][62][63] An in-depth analysis of the top 20 predictions, including an analysis of their ATC classification and references to the literature, is presented in Note S11. A comparison with the set of drugs predicted by Gordon et al 14 is also provided in Note S9.…”
Section: Discussionmentioning
confidence: 99%